1984
DOI: 10.1038/ki.1984.112
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and proteinuria: Long-term sequelae of uninephrectomy in humans

Abstract: Renal function and blood pressure were assessed in 52 renal allograft donors 10 years or more following uninephrectomy, and their current function compared to their pre-uninephrectomy function as well as to age- and sex-matched control subjects consisting of inpatient potential renal donors and a normal "outpatient" population. The results show no significant deterioration in renal function as determined by serum creatinine or creatinine clearance, as a function of years post-uninephrectomy or age at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2
3

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(114 citation statements)
references
References 24 publications
6
103
2
3
Order By: Relevance
“…This difference increased with time from donation, suggesting a progressive effect. Higher levels of proteinuria are seen in donors with hypertension, [38][39][40] and males are at greater risk than females. 41 More recently, Ibrahim et al 35 reported that in 255 donors selected randomly from 3698 nephrectomies performed at the University of Minnesota between 1963 and 2007, 11.5% had microalbuminuria, whereas 1.2% had macroalbuminuria at a mean of 12.2 years after donation.…”
Section: Proteinuriamentioning
confidence: 98%
“…This difference increased with time from donation, suggesting a progressive effect. Higher levels of proteinuria are seen in donors with hypertension, [38][39][40] and males are at greater risk than females. 41 More recently, Ibrahim et al 35 reported that in 255 donors selected randomly from 3698 nephrectomies performed at the University of Minnesota between 1963 and 2007, 11.5% had microalbuminuria, whereas 1.2% had macroalbuminuria at a mean of 12.2 years after donation.…”
Section: Proteinuriamentioning
confidence: 98%
“…The (10,11,13,19,25). The sum of the results of these five studies can be interpreted as showing that there is likely an increase in hypertension and proteinuria in male donors and, not unexpected, a loss of renal function of at least 20% in both genders.…”
Section: Comparisons and Controlsmentioning
confidence: 99%
“…There is a minimal incidence of hypertension and proteinuria in women ~20 years after kidney donation, and this is lower than in male kidney donors. 50 Although the parity of the female subjects in this study was not reported, it is likely that many underwent 1 or more pregnancies. 50 In another study, all indices of renal function were normal 8 years after kidney donation and after an average of 2 pregnancies.…”
Section: Long-term Effects Of Pregnancy On the Kidney When Maternal Rmentioning
confidence: 95%
“…50 Although the parity of the female subjects in this study was not reported, it is likely that many underwent 1 or more pregnancies. 50 In another study, all indices of renal function were normal 8 years after kidney donation and after an average of 2 pregnancies. 51 Although after 17 years and an average of 2 pregnancies, Davison 33 reports a slight (~10%) decline in GFR in women who had donated kidneys.…”
Section: Long-term Effects Of Pregnancy On the Kidney When Maternal Rmentioning
confidence: 95%